Disputes over the governance of reproductive autonomy in Latin America and the Caribbean - Ferretto, Martina (2024)
The transnational collective action in defense of voluntary abortion, known as the “green tide” since the end of 2017, is here to stay and has attracted the attention of the media, academics, and governments. The emergence of this phenomenon, current and in movement, has been studied and analyzed from various perspectives that have enriched our understanding of it. However, it has not been explored much from the analytical perspective of regional governance, as a framework to consider the influence of this phenomenon on rule negotiation processes. This article seeks to contribute to the analysis of the situation of abortion rights in Latin America and the Caribbean within this framework and through a qualitative methodology. The article examines the contributions of transnational articulations of abortion activists and official documents of international organizations, within a novel perspective that combines studies of global governance and critical feminist approaches to international relations. With the aim of underscoring some pending challenges, in addition to highlighting important achievements, it is concluded that the place occupied in multilateral negotiation processes by transnational feminist movements and articulations that fight for expanded rights is significant.